SURVIVAL OF DIFFERENT BACTERIAL SPECIES ON CEMENT AND PORCELAIN SURFACES. AT LOW TEMPERATURE. - A.Razzak , Ahlam (The Iraqi Journal of Veterinary Medicine, 1996)
Fourteen different bacterial species were used in a study of their abilities to survive on cement and porcelain surfaces. A dose of 5x10 cfu/drop (50 ul) for each species was used to contaminate each surface. The bacteria used included: Bacillus subtilis, Brucella abortus, Coraynebacterium pyogenes, E.coli, Klebsiella pnemmoniae, Listeria monocytogenes, Pasteurella multocida, Proteus vulgaris, Pseudomonas aergenosa, Salmonella typhi, Staphylococus aureus, Staph. Epidermidis, Streptococcus equi & Strept. Zooepidemicus. After 7, 14 and 21 days of storage at 4°C, subsamples were cultured onto different types of media, and after 24-48 hr. of incubation at 37°C, growth or no growth were scored for each type of bacteria used. Results showed that B. subtilis, Staph.epidermidis & Strept. zooepdemicus were recovered from all surfaces up till 21-day storage. E. coli, Pr.vulgaris, Staph. aureus & Strept.equi were recovered only from Porcelaim surfaces throughout the whole experiment, whereas Past. multocida was recovered at all times from cement surfaces only. Br. abortus was recovered only from cement surfaces after 7 & 14 days of storage, but was never isolated from contaminated Porcelain surfaces. Kl. pneumoniae was isolated from Porcelain surfaces at all times, but only after 7-day- storage from cement surfaces. On the other hand, L. monocytogenes was never recovered from any surface at any time of storage.